TRANSPARANSI INFORMASI PERUSAHAAN PADA BURSA EFEK INDONESIA, SINGAPURA, DAN THAILAND - AUREL SEPTIAN CHRISTPRATAMA; TARSISIUS RENALD SUGANDA; FITRI OKTARIANI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The aim of this research is to prove the influence of legal system, economic development, inflation, culture, board size, proportion of independent directors, and ownership concentration to the level of disclosure in three countries namely Indonesia, Singapore and Thailand. The research sample consist of 84 listed manufacture companies in Indonesia, Singapore and Thailand Stock Exchange in 2017. Multiple linear regression and anova used in this research. The result showed legal system, economic development, board size and proportion of independent directors had positive effect on e-CTI. However, inflation, culture, ownership concentration did not affect e-CTI. Furthermore, the level of e-CTI in three different countries were identic.